2021
DOI: 10.1159/000518852
|View full text |Cite
|
Sign up to set email alerts
|

Anti-LDL Receptor-Related Protein 2 Nephropathy with Synchronous Primary Kidney Extranodal Marginal Zone Lymphoma

Abstract: <b><i>Introduction:</i></b> Anti-LDL receptor-related protein 2 (anti-LRP2) nephropathy is a rare but progressive form of autoimmune-mediated tubulointerstitial nephritis and glomerular disease, characterized by a classic pattern of immune complex deposition in the kidney. A theoretic link between autoimmune disease and lymphoproliferative diseases exists, and therefore, in some cases autoimmune-mediated inflammation and lymphoproliferative neoplasm can co-exist in the same site. <b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“… 43 Kidney involvement by paraneoplastic Ig deposition most commonly manifests as MN associated with solid-organ malignancies 44 , 45 and infrequently, other conditions. 44 , 46 , 47 Taken together, the cases in our series and review of literature demonstrate that, in comparison to other B-cell lymphomas or plasma cell neoplasms, MCL-associated kidney injury commonly contains C3 or polyclonal immune deposits, suggesting these are driven by systemic immune or complement dysregulation rather than direct deposition of a circulating paraprotein. Mechanisms driving MCL-associated IC disease and underlying immune phenomenon warrant further investigation.…”
Section: Discussionmentioning
confidence: 51%
“… 43 Kidney involvement by paraneoplastic Ig deposition most commonly manifests as MN associated with solid-organ malignancies 44 , 45 and infrequently, other conditions. 44 , 46 , 47 Taken together, the cases in our series and review of literature demonstrate that, in comparison to other B-cell lymphomas or plasma cell neoplasms, MCL-associated kidney injury commonly contains C3 or polyclonal immune deposits, suggesting these are driven by systemic immune or complement dysregulation rather than direct deposition of a circulating paraprotein. Mechanisms driving MCL-associated IC disease and underlying immune phenomenon warrant further investigation.…”
Section: Discussionmentioning
confidence: 51%
“…Three cases of ABBA disease associated with concurrent kidney infiltration by low-grade B cell lymphoma have previously been described. 7 , 14 ABBA disease has also been reported with renal clear cell carcinoma. 3 LRP2/megalin is expressed in a wide range of tissues, including the choroid plexus, the lung alveoli, the thyroid and parathyroid glands, and retina, in addition to proximal tubular cells within the kidney, and has been implicated in tumorigenesis in a range of human cancers, including colorectal cancer, melanoma, and lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Segmental subepithelial immune deposits have been previously described in LRP2-associated ABBA disease but do not stain with anti-LRP2 antibodies, and the presumed podocyte antigen(s) have not been identified. 8 , 14 Staining for the phospholipase A2 receptor (PLA2R) or other podocyte antigens known to be associated with membranous nephropathy was not performed in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, a total of 7 patients with ABBA with concurrent kidney diseases were reported, including minimal change disease, 6 LN, 7 IgG4-related kidney disease, 8 and lymphoma. 9 , 10 A second kidney disease diagnosis was identified in the majority of patients (56.7%), of which included MN, IgA nephropathy, LN, minimal change disease, primary focal segmental glomerulosclerosis, crescentic GNs, nodular diabetic glomerulosclerosis, amyloid light chain amyloidosis, acute interstitial nephritis, granulomatous interstitial nephritis, renal involvement by lymphoma or amyloidosis, arterionephrosclerosis, or antibody-mediated rejection. The histopathologic spectrum of ABBA has broadened with improved recognition, facilitated by the use of LRP2 immunostaining for disease confirmation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…These concurrent kidney diseases included minimal change disease ( n = 1), 6 LN ( n = 2), 7 plasma cell-rich interstitial nephritis ( n = 1), 8 and low-grade B-cell lymphoma ( n = 3). 9 , 10 …”
mentioning
confidence: 99%